Determination of a conformational change in filamin A with Förster resonance energy transfer - Seppälä, Jonne (2011)
Filamins are large rod-like proteins that cross-link actin filaments into three-dimensional networks. They also bind to a plethora of proteins with distinct functions showing that they have a versatile role in cells. Functional filamins are dimers consisting of an N-terminal actin binding domain followed by 24 immunoglobulin-like domains. The most C-terminal domains mediate the dimerization. Two hinge regions are located between the domains 15 and 16 and 23 and 24, respectively, and produce structural flexibility that is essential for the protein function. The domains 18-19 and 20-21 are folded in a pairwise manner in which the first β strands of the even numbered domains are folded along with the odd numbered domains. Recent study implies that a focal adhesion protein migfilin binding replaces the β strand of the domain 20 inducing a conformational change in filamin A that makes its structure more flexible. Previously only stretching force induced conformational changes have been reported and they are thought to function as a mechanism to sense tension. The aim of this study was to demonstrate the migfilin induced conformational change using Förster resonance energy transfer (FRET). Enhanced green fluorescent protein (EGFP) was cloned to the C-terminus of a four domain fragment of filamin A which was first mutated to have a unique site for the acceptor fluorophore conjugation. Then, the recombinant fusion protein was expressed overnight and subsequently purified with affinity chromatography and gel filtration. Finally, the purified protein was labeled with Alexa Fluor 532 C5 maleimide to produce a FRET pair. The change in the energy transfer efficiency upon migfilin addition was measured with steady-state and time-resolved fluorescence methods. No statistically significant change in the amount of energy transfer was observed. The reason is unclear, though it is possible that the EGFP disrupted the dynamics of filamin A or that the migfilin binding was abolished. However, it is also possible that the used method was not sensitive for the possible conformational change in the construct. Changes in the construct are required in further studies.